Legal Regulation of Online Commodity Evaluation Behaviors - Zhou, Xinyu; Rui, Xiulingjia; Wang, Yanping (Pacific International Journal, 2025)
Online commodity evaluation behaviors entail influencers disseminating experiential insights and empirical testing results to evaluate products for consumers. These behaviors have transformed from information tools into market-influential business paradigms. However, regulatory inadequacies spanning administrative supervision, civil liability, and self-regulation have turned them into both consumer rights infringements and market disruptors, manifesting as both overt and covert malpractices. A regulatory framework that incorporates an administrative regulatory paradigm of access filing and risk-classified supervision, a legal regulatory pathway that involves improving identification methods and refining legal elements, and a collaborative governance system that includes platform supervision, industry self-regulation, and consumer association verification should be developed in the future. This framework aims to bring misused tools back to the right track, repair consumer trust, and reshape market order.